2020
DOI: 10.1161/circulationaha.119.043319
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Fatty Acid Oxidation Prevents High-Fat Diet–Induced Cardiomyopathy Through Regulating Parkin-Mediated Mitophagy

Abstract: Background: Increased fatty acid oxidation (FAO) has long been considered a culprit in the development of obesity/diabetes induced cardiomyopathy. However, enhancing cardiac FAO by removing the inhibitory mechanism of long-chain fatty acids transport into mitochondria via deletion of acetyl-CoA carboxylase 2 (ACC2) does not cause cardiomyopathy in non-obese mice, suggesting that high FAO is distinct from cardiac lipotoxicity. We hypothesize that cardiac pathology associated obesity is attributable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
111
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 142 publications
(119 citation statements)
references
References 55 publications
8
111
0
Order By: Relevance
“…Diet induced obesity increases triglyceride storage in multiple tissues causing lipotoxicity that can alter mitochondrial architecture and function, inducing swelling with reduced cristae density (33, 34) . EM revealed such mitochondrial changes as well as myocardial lipid accumulation in both OVX and male mice treated with placebo, and both features improved with PDE9-I (Figure 4f, Figure S5a, S5b).…”
Section: Resultsmentioning
confidence: 99%
“…Diet induced obesity increases triglyceride storage in multiple tissues causing lipotoxicity that can alter mitochondrial architecture and function, inducing swelling with reduced cristae density (33, 34) . EM revealed such mitochondrial changes as well as myocardial lipid accumulation in both OVX and male mice treated with placebo, and both features improved with PDE9-I (Figure 4f, Figure S5a, S5b).…”
Section: Resultsmentioning
confidence: 99%
“…The most recognized mitophagy pathway in mammalian cells is dependent on Parkin 10 . A study revealed that Parkin-related mitophagy promotes cardiomyocyte death in IRI 11 . Another study has indicated that deficiency of autophagy aggravates tubular injury in proximal tubules and leads to damage of mitochondria in IRI-induced AKI model 12 .…”
Section: Introductionmentioning
confidence: 99%
“…Mitophagy is generally considered to play protective roles in the heart although excessive mitophagy can be detrimental under certain conditions (Song et al, 2015a;Nah et al, 2017). The protein levels of PINK1 and Parkin are decreased in the hearts of both type 1 and 2 diabetic animals (Xu et al, 2013;Tang et al, 2015;Shao et al, 2020), suggesting that mitophagy may be inhibited in the diabetic hearts. Using a novel dual fluorescent mitophagy reporter termed mt-Rosella, we labeled and traced mitochondrial fragments that are sequestered by the autophagosome and delivered to and degraded in the lysosome (Catanzaro et al, 2019;Kobayashi et al, 2020a).…”
Section: Introductionmentioning
confidence: 99%